Pengaruh pemberian bahan organik pada tanah liat dan lempung berliat terhadap kemampuan mengikat air - Yazid Ismi Intara; Asep Sapei; . Erizal; Namaken Sembiring; M. H. Bintoro Djoefrie (Jurnal Ilmu Pertanian Indonesia, 2011)
Amount of water that obtained soil depend on soil ability to quick absorp and continue water accepted from soil surface. Water holding capacity of soil are influenced by soil texture and organic matter. The purpose of th is research was to study soil water holding capacity on two textures of soils l.e. clay, and clay loam by organic matter application of chicken manure and compost. Those treatments were control, combined of chicken manure different texture soils, and combined of compost different texture soil. Chicken manure and compost application consisted of two levels of 30 9 5 kg-l soil texture and 50 9 5 kg-l soil texture, respectively. Soil texture consisted of two kinds l.e, clay, and clay loam. The research was analyzed according to descriftive method. Result of this research indicated that the highest available water capacity of 17.352 % was given by combined t reatment of 50 9 compost of 5 kg clay textured soils. The lowest evaporation rate had occur at clay texture soils.